Lifestyle of patients with diabetes mellitus type 1: a systematic review - Carvalho Sales-Peres, Silvia Helena de (2016)
The aim of this review was to verify data concerning the relationship between the existent lifestyle and glycemic control in patients with Diabetes Mellitus Type 1 (DM1). The methods applied included the literature search strategy, selection of studies by means of inclusion and exclusion strategies, according to the characteristics of the studies. The search was conducted in the Lilacs, Medline, PubMed, Cochrame, SciELO and IBECS databases between in the period between 2005 and 2014. The articles selected were studies in humans, investing lifestyle, physical activities and glycemic levels. Of the 1798 studies initially identified, 11 met the eligibility criteria. Among the studies analyzed, 1 cohort; 1 longitudinal prospective, 1 case control and 8 transversal studies that approached the proposed theme were related. Regular physical activity was the variable that presented greatest relationship with the improvement in glycemic levels. Healthy active life, balanced diet, physical activities and education in diabetes improved the glycemic control of the DM1 patient. The results allowed the authors to conclude that a lifestyle based on physical activities interfered directly in the health of patients with DM1, in addition to contributing the glycemic control.